The association between plasma chemokines and breast cancer risk and prognosis: A mendelian randomization study - Yu, Xingxing; Zhang, Yanyu; Lin, Yuxiang; Zou, Shuqing; Zhu, Pingxiu; Song, Mengjie; Fu, Fangmeng; Yang, Haomin (Frontiers in Genetics, 2023)
Background: Despite the potential role of several chemokines in the migration of cytotoxic immune cells to prohibit breast cancer cell proliferation, a comprehensive view of chemokines and the risk and prognosis of breast cancer is scarce, and little is known about their causal associations. Methods: With a two-sample Mendelian randomization (MR) approach, genetic instruments associated with 30 plasma chemokines were created. Their genetic associations with breast cancer and its survival by molecular subtypes were extracted from the recent genome-wide association study, with available survival information for 96,661 patients. We further tested the associations between the polygenetic risk score (PRS) for chemokines and breast cancer in the UK Biobank cohort using logistic regression models, while the association between chemokine expression in tumors and breast cancer survival was analyzed in the TCGA cohort using Cox regression models. Results: Plasma CCL5 was causally associated with breast cancer in the MR analysis, which was significant in the luminal and HER-2 enriched subtypes and further confirmed using PRS analysis (OR=0.94, 95% CI=0.89-1.00). A potential causal association with breast cancer survival was only found for plasma CCL19, especially for ER-positive patients. In addition, we also found an inverse association between CCL19 expression in tumors and breast cancer overall and relapse-free survival (HR=0.58, 95% CI=0.35-0.95). Conclusion: We observed an inverse association between genetic predisposition to CCL5 and breast cancer, while CCL19 was associated with breast cancer survival. These associations suggested the potential of these chemokines as tools for breast cancer prevention and treatment.